(untitled) (Third Sector Social Economic Review, 2017)
Agriculture sector has vital importance in point of the nutrition of community, labour, productivity, economy and the contribution to the exportation in Turkey. . Therefore, it is required to increase the productivity by improving the economic and social aspects of people who live in countryside in where agricultural production is done intensely; increasing the employment opportunities for them; providing social justice for them; and equipping them with education and information in every aspect. One of the most controversial problem in Turkey is that producers are not organized. Cooperatives are at the core of agricultural producers’ organizations. Cooperatives mean a historical accumulation, specific principals and certain cultural structure with a special structure and characteristic that can be connoted as the culture of cooperatives. With its impacts and the benefits on the developments of the culture of democracy and its role in the development of a nation, it must be kept on the agenda and searching for solution is very important. The current situation of agricultural producer organizations which are active in Aydın, the socioeconomic structure of producers, their perspective to the organization, their knowledge level in point of organizing, their expectations from organizing, and their problems in organizing were determined and solution suggestions against these problems were improved by this research. In the study, 3 districts (Söke, Germencik, Koçarlı) with the most cotton production in Aydın province were included in the research. The number of producers to represent cotton producers in Aydın Province was calculated with proportional sampling method and the required sample size was found to be 96. Sampling method was distributed taking account of cotton production. Accordingly, 61 farmer from Söke, 23 farmer from Germencik and 12 farmer from Koçarlı were interviewed. Accordingly, results were summarized as tables and graphics. The normal distribution test was done with the Kolmogorov-Smirnov test for continuous variables. It was determined that the variables did not show normal distribution. Kruskal-Wallis test and Mann-Whitney U test were applied for the variables. As a result of the research, it was determined that the level of agricultural organization of farmers is high. But, this situation differs from organization to organization. Farmers think that the most problems of agricultural organizations are management, funding and education. And they think that agricultural organizations should be controlled only by government.